Measurement of ERP Utilization Level of Enterprises: The Sample of Province Aydın - Özel Sebetci (İşletme Araştırmaları Dergisi, 2014)
The aim of this study is to measure ERP usage level of enterprises in Aydın. Data was obtained from 83 enterprises in Aydın via questionnaires. Data analysis showed that the enterprises had mostly high level of the computer integration and technologies on production. However, it was found that these enterprises did not use ERP systemsat high levels. Correlations between enterprise size by the number of employees, company revenue at 2012 and ERP usage levels were established by chi square test. Correlation analysis showed that there was a significant and positive correlation between ERP characteristics and strategic advantages about ERP.